2010
DOI: 10.1186/1756-3305-3-28
|View full text |Cite
|
Sign up to set email alerts
|

Canine vector-borne diseases in India: a review of the literature and identification of existing knowledge gaps

Abstract: Despite the combination of favourable climate for parasites and vectors, and large populations of stray dogs, information concerning the epidemiology, diagnosis and management of canine vector-borne diseases in India is limited. However, with the country's expanding economy and adaptation to western culture, higher expectations and demands are being placed on veterinary surgeons for improved knowledge of diseases and control. This review aims to provide an overview of the current state of knowledge of these di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 65 publications
(65 reference statements)
1
32
0
Order By: Relevance
“…Although no attempt was made in the present study to characterize B. canis at the subspecies level, in view of detection of R. sanguineus ticks in the body of suspected dogs during the present investigation, it is suggested that B. canis might belong to B. canis vogeli. Megat Abd Rani et al (2010) opined that B. vogeli and B. gibsoni were likely co-endemic in India. Our study also revealed that a large number of Babesia positive cases had co-infections with B. gibsoni and B. canis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no attempt was made in the present study to characterize B. canis at the subspecies level, in view of detection of R. sanguineus ticks in the body of suspected dogs during the present investigation, it is suggested that B. canis might belong to B. canis vogeli. Megat Abd Rani et al (2010) opined that B. vogeli and B. gibsoni were likely co-endemic in India. Our study also revealed that a large number of Babesia positive cases had co-infections with B. gibsoni and B. canis.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of the causal agents involved in cases of canine babesiosis in a particular locality is important to define treatment planning for a successful outcome (Boozer and Macintire 2003). In India, the situation of canine babesiosis is not clear (Megat Abd Rani et al 2010) except few reports (Sundar et al 2004;Chaudhuri 2006;Chaudhuri and Varshney 2007;Senthil Kumar et al 2009;Balachandran et al 2010;Karunakaran et al 2011) that are also based on conventional method of diagnosis and moreover very little study has been done in the North-Eastern region of India. The present communication reports the results of detection of Babesia infection in dogs of Assam, a northeastern state of India, through conventional and molecular methods.…”
Section: Introductionmentioning
confidence: 99%
“…In India, the situation of canine babesiosis is not clear[ 35 ] except few reports. [ 36 37 38 39 40 41 ] The prevalence of canine babesiosis in Assam has been reported as 21.7% without mentioning the species.…”
Section: Hostmentioning
confidence: 99%
“…The Indian dog population is estimated at 25 million of which 5 million are pets and the rest 80 % are family, community or feral dogs (Megat Abd Rani et al 2010). These populations of dogs have been identified to serve as host for various hemoprotozoan parasites which include Babesia gibsoni, Babesia canis, Ehrlichia canis, Hepatozoon canis and Trypanosoma evansi.…”
Section: Introductionmentioning
confidence: 99%